Synthesis of an Azide- and Tetrazine-Functionalized [60]Fullerene and Its Controlled Decoration with Biomolecules - Gulumkar Vijay; Tähtinen Ville; Ali Aliaa; Rahkila Jani; Valle-Delgado Juan José; Äärelä Antti; Österberg Monika; Yliperttula Marjo; Virta Pasi (AMER CHEMICAL SOC, 2022)
Bingel cyclopropanation between Buckminster fullerene and a heteroarmed malonate was utilized to produce a hexakis-functionalized C60 core, with azide and tetrazine units. This orthogonally bifunctional C60 scaffold can be selectively one-pot functionalized by two pericyclic click reactions, that is, inverse electron-demand Diels-Alder and azide-alkyne cycloaddition, which with appropriate ligands (monosaccharides, a peptide and oligonucleotides tested) allows one to control the assembly of heteroantennary bioconjugates.